2020
DOI: 10.1186/s12885-020-07184-7
|View full text |Cite
|
Sign up to set email alerts
|

Low dose environmental radon exposure and breast tumor gene expression

Abstract: Background The International Agency for Research on Cancer classified radon and its decay-products as Group-1-human-carcinogens, and with the current knowledge they are linked specifically to lung cancer. Biokinetic models predict that radon could deliver a carcinogenic dose to breast tissue. Our previous work suggested that low-dose radon was associated with estrogen-receptor (ER)-negative breast cancer risk. However, there is limited research to examine the role of radon in breast cancer biology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Additionally, cumulative radon exposure was associated with higher risk of ER negative breast cancer. The P38 MAPK signaling and phosphocholine synthesis gene sets were significantly enriched in ER negative breast tumor and ER negative normal-adjacent samples with higher cumulative radon exposure [ 3 ]. As the outermost organ of the human body, the skin suffers from environmental damage to agents such as air pollution and cigarette smoking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, cumulative radon exposure was associated with higher risk of ER negative breast cancer. The P38 MAPK signaling and phosphocholine synthesis gene sets were significantly enriched in ER negative breast tumor and ER negative normal-adjacent samples with higher cumulative radon exposure [ 3 ]. As the outermost organ of the human body, the skin suffers from environmental damage to agents such as air pollution and cigarette smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous radioactive decay of this gas emits high-energy alpha particles that may interact with biological tissues and macro-molecules. Similar to other ionizing radiation, radon and its decay products are mutagenic, as they could lead to single and double-strand DNA breaks, pyrimidine dimer formations, intra-and inter-chromosomal aberrations sister chromatid exchange micronuclei formation and eventually genomic instability [ 3 ]. It is indicated that alpha-particle exposure induces mainly unstable complex chromosome aberrations which do not contribute to radiation-associated cytogenetic risk [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 In a follow-up study, it was found the MAPK signaling and phosphocholine biosynthesis pathways, which have roles in ionizing radiation-induced tumorigenesis, were enriched in estrogen receptor-negative and adjacentnormal samples at radon levels as low as 2 pCi, supporting biological plausibility of an association (False Discovery Rate <25%). 40 No significant associations were found in reported studies, and biological plausibility is only weakly supported, though two cohort studies suggest potential associations. More research is needed to investigate any potential association.…”
Section: Breast Cancermentioning
confidence: 90%
“… 39 In a follow-up study, it was found the MAPK signaling and phosphocholine biosynthesis pathways, which have roles in ionizing radiation-induced tumorigenesis, were enriched in estrogen receptor-negative and adjacentnormal samples at radon levels as low as 2 pCi, supporting biological plausibility of an association (False Discovery Rate <25%). 40 …”
Section: Introductionmentioning
confidence: 99%